Fractures of the calcaneus: current treatment strategies - Rammelt, S; Zwipp, H (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2014)
Displaced, intra-articular fractures of the calcaneus represent a surgical challenge and the ideal choice of treatment remains a subject of continued debate. Open reduction and stable internal fixation without joint transfixation has been established as the standard treatment for most of these fractures with good to excellent results in more than two thirds of patients in larger clinical series. The extended lateral approach respects the neurovascular supply to the heel and allows a good exposition of the fractured lateral wall, the subtalar and calcaneocuboid joints, but wound healing problems cannot be completely avoided despite meticulous soft tissue handling. Percuatneous and less invasive procedures have successfully lowered the rates of wound complications but exact anatomic reduction remains an important issue. Care must be taken not to overlook atypical fractures like sustentacular fractures and fracture-dislocations of the calcaneus that are treated with a small medial or curved epimalleolar lateral approach, respectively. The use of bone grafting or bone substitutes for defect filling appears not necessary in most cases. Prognostic factors that can be influenced by the surgeon are anatomical reduction of the overall shape of the calcaneus and congruity of the subtalar joint which should both be controlled intraoperatively. Treatment results are adversely affected by severity of injury, open fractures, bilateral fractures, a high body mass index and smoking. Early, stable soft tissue coverage with pedicled or free flaps appears to lower infection rates and improve the functional results after open fractures. Calcaneal malunions and nonunions are disabling conditions resulting from either non-operative treatment or inadequate reduction and fixation of displaced fractures. Deformity correction is tailored to the type of deformity and individual patient needs. Treatment options include lateral wall decompression, in situ- or corrective subtalar arthrodesis and calcaneal osteotomies accompanied by soft tissue-balancing.
Keywords: Minimally Invasive Surgical Procedures; pooperační péče; Calcaneus; fraktury kostí; vnitřní fixace fraktury; patní kost; lidé; Postoperative Care; Fractures, Bone; miniinvazivní chirurgické výkony; radiografie; Radiography; Fracture Fixation, Internal; Treatment Outcome; Emergencies; výsledek terapie; náhlé příhody; Humans